Environmental system threats - Rak, Janusz (Instal, 2020)
Environmental threats have a multi-faceted character. The occurrence of risk in social and economic life results in the development of management methods. Major accidents may even be cross-border in nature. Public authorities at every level have a duty to alert citizens to threats. The right to information guarantees action to reduce risk. The paper presents examples of international conflicts over water. Reference was also made to start prevention processes and their possible repairs.